Cover Feature: The Trifluoromethyl Sulfinyl and Oxathiyl Radicals (Chem. Eur. J. 7/2018). Issue 7 (7th December 2017) - Wu, Zhuang; Xu, Jian; Deng, Guohai; Chu, Xianxu; Sokolenko, Liubov; Trabelsi, Tarek; Francisco, Joseph S.; Eckhardt, André K.; Schreiner, Peter R.; Zeng, Xiaoqing
Abstract : Two hitherto unreported sulfur‐centered radicals —the trifluoromethyl sulfinyl radical and the trifluoromethyl oxathiyl radical, were generated in the gas phase and then trapped in solid noble gas matrices for characterization with IR and UV/Vis spectroscopy. Subsequent UV light irradiation resulted in an unprecedented isomerization from a sulfinyl radical to an oxathiyl radical by surmounting a formidable activation barrier, despite that such geometrical transformation has been computationally predicted for decades. More information can be found in the Communication by J. S. Francisco, P. R. Schreiner, X. Zeng et al. onpage 1505 .